The Implication of Lecture-Based Learning and Inquiry-Based Learning on Writing and Reading Score of TOEFL-IBT - Kaloeti, Ade Kristianus (International Journal of Education, Information Technology, and Others, 2024)
This study aims to investigate the impact of implementing Lecture-Based Learning and Inquiry-Based Learning methods on the Writing and Reading scores of the TOEFL-IBT. The research adopts a quantitative approach and employs an associative research design. A sample of 40 participants was selected using purposive sampling from the population of students at Universitas Kristen Immanuel, subsequently divided into two classes that utilized different teaching methods. Data, consisting of Writing and Reading scores, were collected through TOEFL-IBT test results from the two classes, each employing a distinct learning method. The data were then analyzed using both multivariate and univariate MANOVA tests. The findings indicate a significant difference in Writing and Reading scores between the two classes that applied Lecture-Based Learning and Inquiry-Based Learning methods. While the applied methods had a simultaneous effect on Writing and Reading scores, the distinct methods exhibited a more pronounced influence on Writing scores compared to Reading scores in the TOEFL-IBT assessment.